1988
DOI: 10.1111/j.1439-0434.1988.tb04472.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Pratylenchus coffeae and Pythium aphanidermatum and/or Rhizoctonia solani on Chrysanthemum*

Abstract: The interaction between Pratylenchus coffeae and Pythium aphanidermatum and/or Rhizoctonia solani on chrysanthemum and the influence of farmyard manure (FYM) on it was studied under pot conditions. The disease caused by P. aphanidermatum or R. solani was significantly high at var\'ing inocuiutn levels of Pratylenchus coffeae. The severiy further increased when nematode infected plants were inoculated with both the fungi together. Organic manunng also influenced the disease severity which was greatest in soils … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…In some studies, it has been reported that nematode penetration was enhanced by formation of fungal pathogen enzymes in the roots (Edmunds & Mai, 1966a, 1966bNordmeyer & Sikora, 1983). Although root lesion nematodes have a different trophic behavior to RKNs, there are studies that show interaction between these nematodes and plant pathogenic fungi increases the nematode density (Vrain, 1987;Hasan, 1988). Also, the lowest number of galls and egg masses in all tomato hybrids in the present study was with treatment FORL+10N because of the root rot caused by FORL affected the nematode feeding process in the root tissues and then negatively affected nematode reproduction.…”
Section: Resultsmentioning
confidence: 50%
“…In some studies, it has been reported that nematode penetration was enhanced by formation of fungal pathogen enzymes in the roots (Edmunds & Mai, 1966a, 1966bNordmeyer & Sikora, 1983). Although root lesion nematodes have a different trophic behavior to RKNs, there are studies that show interaction between these nematodes and plant pathogenic fungi increases the nematode density (Vrain, 1987;Hasan, 1988). Also, the lowest number of galls and egg masses in all tomato hybrids in the present study was with treatment FORL+10N because of the root rot caused by FORL affected the nematode feeding process in the root tissues and then negatively affected nematode reproduction.…”
Section: Resultsmentioning
confidence: 50%
“…However, interactions between Pratylenchus spp. and R. solani have been reported in other crops (Hasan 1988;Kenyon et al 2007). In one of our experiments the most severe stunting developed where onions were grown in soil infected with both AG 8 and Pratylenchus.…”
Section: Discussionmentioning
confidence: 93%
“…It has been reported in alfalfa that seedlings infested with F. oxysporum were more attractive to Pratylenchus penetrans than were healthy seedlings (Edmunds & Mai, 1967). Most of the reports of interactions between nematodes and fungi showed that the nematode populations were favoured by the presence of the fungi (Faulkner & Skotland, 1965; Vrain, 1987; Hasan, 1988). Such an effect may have applied in the present work with most fungal combinations.…”
Section: Discussionmentioning
confidence: 99%